Performance of the State Civil Apparatus (ASN) at the Population and Civil Registry Office of Supiori Regency - Amiruddin Amiruddin; Markus Firdinan Semuel; Rijal Rijal (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study aims to describe and analyze the performance of the State Civil Apparatus at the Population and Civil Registration Service of Supiori Regency. This research is descriptive with a qualitative approach. With data analysis techniques through observation (observation), in-depth interviews (in-depth interviews), documentation (documentation), and literature studies which include the Performance of the State Civil Apparatus in improving public services at the Population and Civil Registration Office of Supiori Regency. Analysis of the Performance of the State Civil Apparatus (ASN) at the Population and Civil Registry Office of Supiori Regency shows that the performance of employees at the Population and Civil Registration Service has not been good and optimal and really needs to be improved, especially on indicators of timeliness, quality and quantity of services. On the indicator of timeliness which is the focus of the problem in the performance of the employees of the Population and Civil Registration Office in Supiori Regency, the level of discipline of employees is still low in completing their duties. In terms of service quality, it needs to be improved because there is still a lack of supporting facilities and infrastructure, especially existing device technology and there are still public complaints in terms of inadequate service places, in terms of service quantity measured by the level of community satisfaction receiving services is still low and needs to be improved, In addition, the leadership of the Population and Civil Registration Service employees needs to be improved in order to improve the performance of the existing ASN. Factors that affect the performance of ASN in the Population and Civil Registration Service in the Supiori Regency in public services are the productivity of services carried out by employees is very influential on employee performance and it needs to be improved. significant in accordance with applicable regulations. From Responsibility, it still needs to be improved and improved, this greatly affects the performance assessment to measure the level of satisfaction of the community being served, while judging by Accountability, it can be seen that there are still differences in attitudes shown by employees in providing services, where these differences are a form of injustice in providing services to the community, both That's the difference in.